Varying results of early benefit assessment of newly approved pharmaceutical drugs in Germany from 2011 to 2017: A study based on federal joint committee data. Issue 1 (30th January 2019) - Peinemann, Frank; Labeit, Alexander
Abstract: Background: Since January 2011, the Federal Joint Committee (FJC) conducts early benefit assessments (EBA) of newly approved pharmaceutical drugs compared to appropriate standard therapies. The FJC commissions the Institute for Quality and Efficiency in Healthcare (IQEH) to prepare preliminary reports. We aimed to evaluate the extent, impact, and reason for different judgments on added benefit of both institutions. Methods: We searched EBA data on the FJC website and included completed procedures from 2011 to 2017. We conducted a quantitative analysis of the difference between FJC and IQEH on divergent judgments, a quantitative analysis of the impact of EBA on market withdrawal, and a qualitative analysis to identify potential factors contributing to divergent judgments. Results: FJC rated an added benefit in 30% (139 of 457) and IQEH in 22% (101 of 457) matching research questions ( P = 0.004). In the aftermath of EBA, 28 pharmaceutical drugs were withdrawn from the German market. We identified three potential factors that might have contributed to the divergent judgments. IQEH used a unique threshold concept to define the rating, FJC conducted additional public hearings, and FJC showed more flexibility with adherence to stringent criteria and interpretation of results. Conclusions: FJC and IQEH differed significantly in their early benefit assessment. In response to negative EBA decisions, pharmaceutical companies withdrew a considerable number of medicines from the German market. The present work uncovers the subjectivity and possible variance inherent in benefit assessment, as the two institutions observe the same rules of procedure.